Physiology of wheelchair racing in athletes with spinal cord injury - Bhambhani, Y. (Sports Medicine, 2002)
Wheelchair racing is one of the most popular sporting activities of individuals with spinal cord injury. Athletes with this impairment have unique changes in metabolic, cardiorespiratory, neuromuscular and thermoregulatory systems, which reduce their overall physiological capacity compared with able-bodied individuals or individuals with other types of impairments. This review on spinal cord injury: (i) presents the International Stoke Mandeville Games Federation classification of wheelchair athletes; (ii) describes methods commonly used to characterise anaerobic and aerobic fitness; (iii) presents the findings of physiological studies that have evaluated wheelchair racing performance; (iv) identifies the risks associated with temperature regulation when competing in wheelchair races; and (v) discusses special conditions that can influence wheelchair racing performance.